Information communication technology elements for productive aging in future technology / Akmal Hikmah Mohd Nasir - Mohd Nasir, Akmal Hikmah (2015)
Elderly people seem to have been a neglected user group in designing of ICT tools and services, although the requirements to create well functioning solutions for them are very well known. The aim of this study is to enlighten these issues based on former research, current observations and interview sessions with current elderly and promote the most desired and needed elements if an ICT tool was to develop specially for them. This study also was done in order to help designers develop products that are more accessible for elderly. In this project, the ICT tool that was highlighted is the smart phone. This is because of the smart phone seems to be the most used among elderly based on earlier observation. The results described in this study are not projected as a new methodology but as a practical means to improve existing methodologies in creating a more elderly friendly ICT tools in future.